Skyhook-PID controller for active railway pantograph - Abdullah, Mohd Azman; Harun, Mohd Hanif; Ahmad, Fauzi; Ibrahim, Munaliza; Mohamed Jamil, Fathiah (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2024)
This article describes a technique for an active pantograph in rail transportation using two different active control technologies to control the vertical displacement between the railway pantograph and the overhead contact line. The performance of proportional-integral-derivative (PID) controllers and skyhook PID controllers based on disturbances such as step, sinusoidal, and random inputs was investigated. Active traction pantograph systems with Skyhook PID controllers show better performance than passive pantograph systems by Root Mean Square (RMS) analysis. In summary, this simple skyhook PID controller can be proposed for future experimental approach of active railway pantograph.